1993
DOI: 10.1111/j.1467-6494.1993.tb00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Web of Personality Judgments: The Influence of Social Networks on Personality Assessment

Abstract: Contemporary assessment models have focused on the degree to which self- and other reports of personality description agree in an effort to define consensus and agreement about personality attributes. In general, we believe that analyses of this type of data have been limited in that they tend to focus on both simple models (usually dyad-based) and simple aggregations of data (usually correlations between self- and other ratings). In addition, the behaviors used as stimuli in experimental settings lack the ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 52 publications
3
35
1
2
Order By: Relevance
“…However, Openness to Experience was negatively associated with friendship centrality and correlated positively with adversarial centrality. Similar findings were obtained in Kanfer & Tanaka's (1993) study with students. They found that the more Extraverted, Agreeable, and Emotionally stable individuals were better connected in a network.…”
Section: Social Network Analysis and Personalitysupporting
confidence: 90%
“…However, Openness to Experience was negatively associated with friendship centrality and correlated positively with adversarial centrality. Similar findings were obtained in Kanfer & Tanaka's (1993) study with students. They found that the more Extraverted, Agreeable, and Emotionally stable individuals were better connected in a network.…”
Section: Social Network Analysis and Personalitysupporting
confidence: 90%
“…For instance, according to Kanfer and Tanaka [25] all the Big Five personality traits, with the exception of Agreeableness, correlate closely with degree, and more precisely with in-degree; moreover, agreeable persons tend to occupy central positions and report more interacting with others while outgoing (extraverted) and secure (low Neuroticism) subjects had more people reporting interacting with them. Klein et al [26] found negative correlation between in-degree centrality from Neuroticism and Openness, and a positive effect of Agreeableness in friendship networks of work group members.…”
Section: Centrality Measuresmentioning
confidence: 99%
“…Por outro lado, no campo da avaliação da personalidade, inúmeras pesquisas concluíram que informações oriundas de testes de autorrelato, os denominados inventários de personalidade, tendem a ser substancialmente diferentes da maneira como outras pessoas percebem o indivíduo (por exemplo, Clifton, Turkheimer, & Oltmanns, 2004;Kanfer & Tanaka, 1993). Kanfer e Yanaka (1993) sinalizaram os benefícios potenciais da aplicação de métodos de análise de redes sociais para o entendimento das conexões entre avaliação da personalidade e contextos sociais.…”
Section: Resumen -Evaluación De La Personalidad Y De Las Redes Socialunclassified
“…Mehra et al (2001) No campo da avaliação de problemas de personalidade, a inclusão de informantes além do próprio indivíduo não é novidade, e foi recomendada por diversos autores (Fiedler, Oltmanns & Turkheimer, 2004;Kanfer & Tanaka, 1993). Fiedler et al (2004) administraram medidas de transtornos de personalidade nas formas de autorrelato e de relatos de pares a 1080 recrutas do exército e acompanharam os participantes por dois anos.…”
Section: Estudos Envolvendo Personalidade E Redes Sociaisunclassified